Effects and Impact of Selenium on Human Health, A Review - Song Bai; Miaohe Zhang; Shouying Tang; Miao Li; Rong Wu; Suran Wan; Lijun Chen; Xian Wei; Shuang Feng (Molecules)
Selenium (Se) is an essential trace element that is crucial for human health. As a key component of various enzymes and proteins, selenium primarily exerts its biological functions in the form of selenoproteins within the body. Currently, over 30 types of selenoproteins have been identified, with more than 20 of them containing selenocysteine residues. Among these, glutathione peroxidases (GPXs), thioredoxin reductases (TrxRs), and iodothyronine deiodinases (DIOs) have been widely studied. Selenium boasts numerous biological functions, including antioxidant properties, immune system enhancement, thyroid function regulation, anti-cancer effects, cardiovascular protection, reproductive capability improvement, and anti-inflammatory activity. Despite its critical importance to human health, the range between selenium’s nutritional and toxic doses is very narrow. Insufficient daily selenium intake can lead to selenium deficiency, while excessive intake carries the risk of selenium toxicity. Therefore, selenium intake must be controlled within a relatively precise range. This article reviews the distribution and intake of selenium, as well as its absorption and metabolism mechanisms in the human body. It also explores the multiple biological functions and mechanisms of selenium in maintaining human health. The aim is to provide new insights and evidence for further elucidating the role of selenium and selenoproteins in health maintenance, as well as for future nutritional guidelines and public health policies.